Cytotoxicity and antioxidant activities of methanolic extract of Marchantia polymorpha and Dicranum scoparium using network pharmacology, molecular docking, and experimental approaches - Shivom Singh; Gaurav Bhadauriya
A comparative study was conducted to assess the antioxidant activity, cytotoxicity, and molecular docking of methanolic extracts from Marchantia polymorpha (Marchantiaceae) and Dicranum scoparium (Dicranaceae). The species M. polymorpha and D. scoparium remain largely unexplored in terms of their biochemical characterization and potential pharmacological activities. Phytoconstituents in the methanolic extracts were identified using spectral analysis. The cytotoxicity study utilized the MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay with U-87 human glial cell lines, while antioxidant activity was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Additionally, a network pharmacology approach was employed to identify molecular targets in relation to cytotoxicity using the isolated compounds. Molecular docking was performed to evaluate the interactions between the isolated phytoconstituents of M. polymorpha and D. scoparium with the estrogen receptor ESR1 (Estrogen Receptor 1) (PDB ID: 1GWQ). The DPPH assay results demonstratedthat antioxidant activity increased with higher extract concentrations. The percentage scavenging activity ranged from 4.41 to88.05% for M. polymorpha and from 3.69 to 88.46% for D. scoparium, with minimum activity observed at 15.62 (So(Bg/mL andmaximum activity at 1000 (So(Bg/mL. The superoxide radical scavenging activity ranged from 0.00 to 48.09% for M. polymorphaand from 0.00 to 45.39% for D. scoparium. Network pharmacology analysis identified the estrogen receptor (ESR1) as acommon target involved in cancer. Molecular docking studies revealed that quercetin exhibited the strongest interactions withESR1 among all the selected phytoconstituents from M. polymorpha and D. scopariums